Pilotna študija o nasilju v družini - Selič, Polona (Zdravstveno varstvo, 2008)
Background: Domestic violence has considerable impact on the health status of patients. The purpose of this survey was to explore the willingness of the patients to convey their experience of abuse in the family, and to compare patient reports and doctors' observations on domestic violence. Methods: A cross-sectional study on family violence included 27 Slovenian family practitioners, who screened each fifth consecutive patient (totally 1,103 patients) over a period of 14 days. The study investigated the frequency of violence episodes (as reported by the patients to a trustworthy person, i.e. their family physician), the readiness of the victims to seek help, the sensitivity of the physicians to this issue, and their qualifications/aptitudefor immediate help/intervention. Results: Exposure to both physical and psychological violence was reported by 141 (12.78 %) patients, physical violence alone by 65 (5.89 %), psychological violence aloneby 120 (10.88 %), whereas 777 (70.44 %) patients denied exposure to any kind of family violence. Conclusions: The exposure of a victim to psychological and/or physical violence in the family is very likely to be recognized by the family physician. However, such patients very rarely seek help from their family doctor. Physicians identified 164 and failed to identify 162 of the 326 self-reported victims of domestic violence. The results show that physicians need additional knowledge and guidelines in the field.
Keywords: nasilje v družini; vloga zdravnika; zlorabe